Perkembangan Pengaturan Tindakan Afirmasi Perempuan Pada Dewan Perwakilan Rakyat Republik Indonesia - Naqiyyah, Ishmah (Jurnal Konstitusi & Demokrasi, 2021)
This research discusses the development of affirmative action arrangements to increase women's representation in the DPR RI and how the implementation of these arrangements since the beginning of affirmative action was applied in 2004 until the last time affirmative action for the DPR was applied, namely in 2014. The research method used is normative juridical with a legal history approach. The discussion begins by analyzing affirmative action in the Political Party Law, the General Election Law for Members of the DPR, DPD, and DPRD, and the Law on the People's Consultative Assembly, the House of Representatives, the Regional Representatives Council, and the Regional Representatives Council. In addition, this study will discuss the law's implementation by analyzing the implementation of regulations. The results of this study show that there are two forms of affirmative action for women to enter the DPR RI, namely through political party quotas and quotas in the legislative nomination process. Every period of filling the position of the DPR, the regulations regarding affirmative action for women constantly change. However, these changes have yet to increase women's representation in the DPR RI significantly.